Semantic reflection of rhetorical expression in brand design (Al-Academy, 2022)
The rhetoric is concerned with the expressive emphasis of things, the science of the statement takes the treatment of graphic images and rhetorical fiction, and in the science of the exquisite dealing with the study of verbal and moral improvements, and in the science of meanings took all related to compositions and methods, and these vocabulary entered into the field of art and its branches largely, especially in the uncle and art of design because it has a major role in including a lot of biological functions with a deep meaning of its comprehensiveness on the multiplicity of real meanings characterized by suggestive and important and semantics refer to the recipient in the research to refer to the recipient The discovery of the internal contents, meanings and meanings of speech, which came through the technical, intellectual, expressive, functional and aesthetic orientation to present multiple show options consistent with the design idea. This research highlighted the extent of the semantic reflection of the brand's rhetorical expression and the presentation of the research problem was based on the question: What is the semantic reflection of rhetorical expression in brand design?The research included four chapters, from which the theoretical framework identified two theories and addressed the following topics: (the intellectual and philosophical vision of the concept of significance, the rhetorical, semantic and deliberative concept of expression in the brand, and the methods of reflecting the expressive significance in the design of the brand), and then addressed the research indicators that produced the theoretical framework, including the semantic interaction of rhetorical expression, representing a structure loaded with formal rather than verbal meanings, crystallized in the embodiment of expressive rhetoric in the design of the brand. The third chapter dealt with the procedures he carried out, which included the methodology of research by selecting the descriptive approach for the purposes of analysis, adopting the method of the sample intended in the selection of sample models, if (5) models were chosen from the research community and by (25%) of the original community, and then singled out the fourth chapter to present the results, discuss them and conclusions, as it came from: Key words (Expression, Rhetorical, reflectance, Significance)1. The eloquence of expression was shown by the suggestive significance of the movement of the arrow, which represents a smile that represents the satisfaction and joy of the consumer, as it was achieved by that indication the strength of the indicator represented by the smiley arrow under the written text as in the models (1.5), but the results include:1. Rhetorical expression is not a compilation of different elements or multiple words in meaning, but rather a mediator who engages and interacts with elements so that their qualities are acquired from each other as a result of the interaction based on organization and order of the elements of the idea.